The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1992
DOI: 10.1016/0377-0273(92)90099-y
|View full text |Cite
|
Sign up to set email alerts
|

A rheological investigation of vesicular rhyolite

Abstract: Res., 50: 307-322.The rheology of vesiculating rhyolitic systems exerts a strong control on the transport of silicic magmas in the subvolcanic to volcanic environments. We present here an investigation of vesiculating and vesiculated rhyolites using dilatometric methods. This study examines the effect of vesicle content on the viscosity of a natural supercooled rhyolitic liquid with 0-70% vesicles.The experimental samples of rhyolitic glass are derived from fusion of a natural obsidian from Little Glass Butte,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 32 publications
5
88
1
Order By: Relevance
“…For example, in the experiments of Lejeune et al (1999) using the Gent-type apparatus typical strain values are in the range 5^30%. Likewise, in the study of Bagdassarov and Dingwell (1992) total strain was reported as several percent. From the simulations presented in Manga and Loewenberg (2001) it is noted that for Ca in the transitional regime, transient rheological e¡ects (thixotropy) are present until total strain exceeds 100%.…”
Section: Rheometric Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…For example, in the experiments of Lejeune et al (1999) using the Gent-type apparatus typical strain values are in the range 5^30%. Likewise, in the study of Bagdassarov and Dingwell (1992) total strain was reported as several percent. From the simulations presented in Manga and Loewenberg (2001) it is noted that for Ca in the transitional regime, transient rheological e¡ects (thixotropy) are present until total strain exceeds 100%.…”
Section: Rheometric Resultsmentioning
confidence: 91%
“…An inconsistency between the exploratory experimental results of Murase (1962) and the analytical results of Taylor (1932) for the dependence of suspension shear viscosity on bubble fraction (P) was noted in the geological literature by Shaw (1965) over 35 years ago. By drawing on results from experimental (Bagdassarov and Dingwell, 1992;Stein and Spera, 1992;Lejeune et al, 1999Lejeune et al, , 2000Spera and Stein, 2000), simulation (e.g., Loewenberg and Hinch, 1996;Manga et al, 1998;Manga and Loewenberg, 2001) and theoretical studies (Schowalter et al, 1968;Frankel and Acrivos, 1970) a consistent picture can be constructed. This picture enables one to estimate the relative shear viscosity of dilute and concentrated magmatic emulsions across the range of shear rates pertinent to natural systems.…”
Section: Emulsion Rheology and Rheodynamic Regimes : A Brief Synopsismentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of crystals and changes in crystallinity can influence viscous flow and the rheological properties of magmas (e.g. Bagdassarov and Dingwell 1992;Smith 1996;Stevenson et al 1996;Manga et al 1998;Griffiths 2000;Pistone et al 2016). However, the Rocche Rosse lava flow is generally a crystal-free glass (with some exceptions; Davì et al 2009Davì et al , 2010, thus crystal content is excluded from calculations.…”
Section: Crust Formationmentioning
confidence: 99%
“…Below 1000°C quartz glass dilatometers are used in our lab employing geometries of axial cylinder compression (e.g. Bagdassarov and Dingwell, 1992) fiber elongation (Webb and Dingwell, 1989) and micropenetration of spheres . These low temperature geometries involve volume and shear components of deformation, at least during initial loading, and care must be taken to obtain time invariant, Newtonian data.…”
Section: Viscositymentioning
confidence: 99%